1995
DOI: 10.2466/pr0.1995.76.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Scores on WISC–III and WRAT–3 for a Sample of Referred Children and Youth

Abstract: This investigation compared the Wechsler Intelligence Scale for Children-III with the Wide Range Achievement Test-3 for a sample of 60 children and youth who were referred for special education services. Pearson product-moment correlations for the criterion measures for the WRAT-3 showed a significant positive association with the WISC-III scores. Implications for concurrent validity between the tests are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…According to these data for this group of referred children, it appears that the results obtained are consistent with earlier studies, (e.g., Smith & Smith, 1986;Vance & Fuller, 1995;and Wright, 1987). The correlations are also consistent with those of the WRAT3 manual (Wilkinson, 1993), although slightly lower.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…According to these data for this group of referred children, it appears that the results obtained are consistent with earlier studies, (e.g., Smith & Smith, 1986;Vance & Fuller, 1995;and Wright, 1987). The correlations are also consistent with those of the WRAT3 manual (Wilkinson, 1993), although slightly lower.…”
supporting
confidence: 82%
“…A recent study of referred children (Vance & Fuller, 1995) reported correlations of .68 (FSIQ WISC-111 with WRAT3 Spelling) to .82 (WISC-111 with WRAT3 Arithmetic). These values are higher than those reported by Wilkinson (1993) and are similar to findings presented in Sattler (1988) on the WISC-R and WRAT-R.…”
mentioning
confidence: 99%
“…The remaining 43 children were screened for intellectual dysfunction using the parts of the Weschler Intelligence Scale for Children-Third Edition (WISC-III) (29), severe learning problems with the Wide Range Achievement Test-Third Edition (WRAT III) (29), and psychiatric disorders with the NIMH Diagnostic Interview Schedule for Children Version 4.0 (DISC-4.0) (30). Four children failed these screening procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The WRAT3 reading subtest is a well-validated, easy-to-administer measure that is frequently used to estimate verbal intelligence (Griffin et al, 2002;Kareken et al, 1995;Letz et al, 2003). Correlations ranging from .45 to .72 (average r approximately .60) have been found between the WRAT3 and the full-scale score on the Wechsler in adults and children (Griffin et al, 2002;Johnstone et al, 1996;Kareken et al, 1995;Vance and Fuller, 1995;Warner et al, 1987;Wiens et al, 1993;Wilkinson, 1993).…”
Section: Methodsmentioning
confidence: 99%